Up-Front and Salvage Transoral Laser Microsurgery for Early Glottic Squamous Cell Carcinoma: A Single Centre Retrospective Case Series - Meulemans, Jeroen; Bijnens, Jacqueline; Delaere, Pierre; Vander Poorten, Vincent (Frontiers in Oncology, 2018)
Introduction/aim Transoral laser microsurgery (TLM) is a minimally invasive surgical alternative for radiotherapy (RT) in the primary management of early glottic cancer. More recently, TLM emerged also as a possible salvage treatment for selected radiorecurrent cancers. We reviewed outcomes of primary and salvage TLM performed in a Belgian tertiary referral center. Patients and methods A retrospective review of records from 142 consecutive patients who underwent TLM was performed. Oncologic outcomes were evaluated by means of descriptive statistics and Kaplan–Meier estimates. Variation of estimated outcomes between different subgroups was evaluated using Log-Rank analysis. Results Of 142 patients, 109 (76.8%) underwent TLM as a primary treatment and 33 (23.2%) were treated in a salvage setting for recurrent or second primary glottic cancer. cT classification in the up-front TLM group was cT1a in 72 (66.1%), cT1b in 11 (10.1%), and cT2 in 26 (23.9%) patients. In the salvage group, patients were cT/rT classified as cT1a–rT1a in 17 (51.5%), cT1b–rT1b in 1 (3.0%), cT2–rT2 in 14 (42.4%), and cT3–rT3 in 1 (3.0%) patients. All patients were cN0. Second-look TLM was performed in 28 patients (19.7%), and RT was associated as adjuvant therapy in 5 patients (3.5%). Mean follow-up was 51.6 months (SD = 38.4 months). Three-year overall survival (OS) was 94.1% (SE = 2.2%), 3-year disease-specific survival (DSS) 100%, 3-year disease-free survival (DFS) 80.1% (SE = 3.8%), 3-year local recurrence-free survival (RFS) 81.0% (SE = 3.7%), and 3-year ultimate local control rate with laser alone 89.2% (SE = 3.0%). Upon subgroup analysis, no differences in OS, DSS, and DFS were observed between the up-front and salvage group (log rank; p = 0.306, p = 0.298, and p = 0.061 respectively). However, local RFS and ultimate local control rate with laser alone were significantly higher in the primary treated TLM group (log rank, p = 0.014 and p = 0.012). Five-year laryngeal preservation rate was 89.7% (SE = 3.5%) in the total population, 100% in the upfront group, and 64.9% (SE = 9.8%) in the salvage group, a difference which proved statistically significant (Log-Rank, p < 0.001). Conclusion This retrospective study confirms excellent oncologic outcomes of up-front TLM for early glottic cancer. In the salvage setting, TLM allows avoidance of total laryngectomy in the majority of cases.